Analysis of the Implementation of Education for Sustainable Development (ESD) Values - Safira, Salma Shafi; Kuswanto, Eko; Pratama, Anisa Oktina Sari (Jurnal Pijar Mipa, 2025)
Education plays a crucial role in supporting the achievement of the SDGs, especially through the integration of ESD principles in the learning process. This study aims to analyze the implementation of ESD values in environmental aspects at Kalirejo 1 Junior High School, which is a provincial Adiwiyata school. This research uses a qualitative approach, collecting data through interviews, observations, questionnaires, and documentation. Data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. Informants in this study included the principal, vice principal for curriculum, science teachers who were also Adiwiyata team leaders, and student representatives from nine extracurricular activities (two students per extracurricular activity). This study evaluated 99 ESD indicators in the environmental aspect, and the results showed that 94 indicators (95%) had been successfully implemented, which include natural resources, climate change, rural development, sustainable urbanization, and disaster prevention and mitigation. These practices have been integrated into the Merdeka Curriculum, both through learning activities and school culture that builds environmental awareness. However, there are still some challenges, namely the non-optimal drainage system and water conservation facilities, such as biopores. This shows that Kalirejo 1 Junior High School has a strong commitment to implementing sustainable education. However, there is still room for improvement so that the implementation of ESD at 1 Kalirejo Junior High School can run more thoroughly, effectively, and sustainably in the future.